The fiction of scarcity: conceptualising scarcity in terms of global justice - Brotherton, Michelle (Rhodes University, Faculty of Humanities, Department of Philosophy)
This thesis intends to contribute to the discourse on global justice as it pertains to resources, the distribution of resources, and the allocation of resources. The focus is on the concept of scarcity. I examine scarcity for how it is understood, interpreted, and applied in the literature on global justice. This thesis argues that scarcity lacks conceptual clarity in the discourse on global justice and argues that if scarcity is misconstrued, the consequences can be severe. Conceptual clarity is thus necessary to ensure that scarcity is properly referred to in the discourse on global justice so that scarcity is not erroneously used when justifications are sought for material deprivation and consequent human suffering. In the process, I will also examine how scarcity is used as a justification in instances of material deprivation and why this is problematic. Given the lack of conceptual clarity regarding scarcity, I argue that reliance on scarcity as justification may be erroneous. The conflation of absolute scarcity and relative scarcity may amount to a category mistake. This thesis purports to clarify scarcity conceptually in the context of global justice. In doing so, I recommend that a resource-centric approach to resource scarcity is adopted to accurately account for the scarcity status of resources. A resource-centric approach to resource scarcity based on a more nuanced understanding of scarcity avoids the potential category mistake. Such an approach ensures that material deprivation and consequent human suffering are not wrongfully attributed to scarcity.
Keywords: Scarcity -- Philosophy; Distributive justice; Political science -- Philosophy; Philosophy; Justification (Ethics); Fallacies (Logic)